Intense low-frequency sound transiently biases human sound lateralisation - Carlos Jurado; Benedikt Grothe; Markus Drexl (PLoS ONE, 2025)
Intense low-frequency (LF) sound exposure transiently alters hearing thresholds and other markers of cochlear sensitivity, and for these changes the term ‘Bounce phenomenon’ (BP) has been coined. Under the BP, hearing thresholds slowly oscillate for several minutes involving both stages of hyper- and hyposensitivity and it is reasonable to assume that the perception of sounds at levels well above threshold will also be affected. Here, we evaluated the effect of the BP on auditory lateralisation in healthy human subjects. Sound lateralisation crucially depends on the processing of either interaural level- or time differences (ILDs and ITDs, respectively), depending on the spectral content of the sound. The ILD needed to perceive a virtual sound source in the middle of the head was tracked across time. Measurements were carried out without and with a previous exposure to an intense LF-sound in the left ear, to elicit the BP. In 65% of the recordings, significant time-variant deviations from the perceived midline were observed after cessation of the LF-sound. In other words, a binaural stimulus perceived in the middle moved perceptually to the side and often back to the middle after presentation of the intense LF-sound. This means that intense LF-sound exposure can lead to a biasing of ILD-based sound localisation.